How to understand sports and traditional games and how to apply it to physical education. On the "Goal of Game" - J. P. Ribas; J. Hernández-Moreno; R. Díaz-Díaz; P. J. Borges-Hernández; J. V. Ruiz-Omeñaca; A. R. Jaqueira (Frontiers Media S.A., 2023)
IntroductionDoes philosopher's stone exist in physical education? It could be said that teaching games for understanding approach (TGfU) keeps turning everything it touches into gold: its presence in the educational centers, its volume of publications, the way of teaching games and sports, its connections with other approaches, its game categories, learning transferable principles of play. But... no, all that glitters is not gold. There are TGfU issues that should be improved. For example, these categories are disconnected from each other because TGfU lacks classification criteria. The "goal of game" is a concept that has been studied, but it has not been applied to physical education. The aim of the article is to show how to deepen the understanding sports and traditional games from the "goal of game", and to propose its applicability to physical education.MethodsThe traits of "goal of game" will be identified by investigating two close concepts, "prelusory goal" (formalist philosophy of sport) and "motor-goal" (motor praxeology).ResultsThe traits of "goal of game" concept: main-motor-problem, described in the game rules and that the players will try to solve during the game dynamics. The "goal of game" chances: (1) It allows us to understand sports and traditional games based on their internal logic (2) It allows us to classify traditional games and sports based on classification criteria and that can be useful to organize the physical education program; (3) It allows us to deepen the understanding of sporting games and their applicability to physical education: on the one hand, proposing progressively more specific goal of game options and, on the other hand, proposing a network model of intentions of play to understand the game dynamics and to design learning tasks.ConclusionsThe conclusions collect some properties of the "goal of game" concept in order to propose its applicability in physical education students learning: identify and compare the main-motor-problems of the games; solve these problems during the game dynamics; transfer the procedures used to solve other games. The goal(d) of game amazes us; maybe physical education teachers are curious to continue discovering this wonderful treasure.